2009
DOI: 10.1021/ol9021194
|View full text |Cite
|
Sign up to set email alerts
|

4-Aminopyridine Catalyzed Direct and Regioselective Acylation of N-Tosylhydrazide

Abstract: An efficient and simple method for selective acylation of either one of two nitrogen atoms of tosylhydrazide was developed. The selectivity was drastically controlled by a catalytic amount of 4-aminopyridine or 4-(dimethylamino)pyridine with common acylating agents. The nitrogen atom masked with a tosyl group was acylated in the presence of 4-aminopyridine, whereas the primary nitrogen atom was acylated in the absence of 4-aminopyridine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
5

Relationship

4
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…Further protections of secondary alcohol and acylhydrazide proceeded smoothly to give 12 by treatment with tert -butyldimethylsilyl trifluoromethanesulfonate as a silylation reagent followed by di- tert -butyl dicarbonate in the presence of a catalytic amount of 4-dimethylaminopyridine. As we expected, Boc protection occurred on the nitrogen possessing the acyl group due to the acidity of NH protons and steric hindrance 49 . Treatment of 12 with triethylsilyl trifluoromethanesulfonate and 2,6-di- tert -butyl pyridine at −78 °C readily afforded silyl ketene aminal, and the crude product was treated with N -bromosuccinimide in a mixed solvent of tetrahydrofurane (THF) and methanol to give bromide 13 in an 82% two-step yield along with 7–14% of starting material 12 .…”
Section: Resultssupporting
confidence: 54%
“…Further protections of secondary alcohol and acylhydrazide proceeded smoothly to give 12 by treatment with tert -butyldimethylsilyl trifluoromethanesulfonate as a silylation reagent followed by di- tert -butyl dicarbonate in the presence of a catalytic amount of 4-dimethylaminopyridine. As we expected, Boc protection occurred on the nitrogen possessing the acyl group due to the acidity of NH protons and steric hindrance 49 . Treatment of 12 with triethylsilyl trifluoromethanesulfonate and 2,6-di- tert -butyl pyridine at −78 °C readily afforded silyl ketene aminal, and the crude product was treated with N -bromosuccinimide in a mixed solvent of tetrahydrofurane (THF) and methanol to give bromide 13 in an 82% two-step yield along with 7–14% of starting material 12 .…”
Section: Resultssupporting
confidence: 54%
“…After the examination of various reaction conditions, we found that the regioselectivity of acylation of N tosylhydrazine depends on the presence of DMAP catalyst, i.e., N,N acyltosylhydrazines are the sole products in the presence of DMAP, whereas N acyl N tosylhydrazines are obtained without DMAP catalyst. 12 Although the origin of regioselectivity with DMAP catalyst is still unclear, investigations to elucidate the mechanism are currently underway in our laboratory. Next, the Hg(OTf) 2 catalyzed cyclization as a key reaction for construction of the E ring system was examined.…”
Section: Synthesis Of E Ringmentioning
confidence: 99%
“…4-Dimethylaminopyridine (DMAP), a hypernucleophilic catalyst, was used to increase the acylation of TANI (with the aliphatic diacyl chlorides). 41 The use of protecting agents was not necessary as the targeted materials were obtained pure and in high yield, as evidenced by NMR, MALDI-TOF MS, FT-IR and elemental analysis. To obtain high quality resolved 1 H NMR spectra of the TANI-E n -TANI materials, phenyl hydrazine was used to reduce the materials to their LEB oxidation states.…”
Section: Synthesis and Characterisation Of Semiconducting Tani-e N -T...mentioning
confidence: 99%